PENYUSUNAN LAPORAN KEUANGAN USAHA MIKRO KECIL MENENGAH BERDASARKAN SAK EMKM (STUDI KASUS DI UMKM KETOPRAK & TAHU GIMBAL IBU SUN) - Arsepti Arsepti; Winanda Winanda (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
This study aims to develop financial statements for UMKM Ketoprak & Tahu Gimbal Ibu Sun based on the Indonesian Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). The business, established in 2015, is a traditional food vendor managed independently without any formal bookkeeping system. All financial activities are conducted solely based on the owner's memory and practical experience, with no written or digital records. Using a descriptive qualitative approach, data were gathered through direct observation and in-depth interviews, then reconstructed into an income statement, statement of financial position, and explanatory notes. The results reveal that even in the absence of formal records, preparing SAK EMKM-compliant financial reports is feasible in a simplified and practical manner. Major challenges include limited time, low accounting literacy, and the lack of regulatory pressure for formal reporting. This study emphasizes the urgent need for continuous guidance and financial literacy training to empower micro-entrepreneurs in managing their business finances more effectively and sustainably.